Quality of life of elderly people with impaired physical mobility - Juliana Maria de Paula; Namie Okino Sawada; Adriana Cristina Nicolussi; Cristiane Thomaz de Aquino Exel Andrade; Viviane Andrade (Universidade Federal do Ceará, 2014)
This is an integrative review, which aimed at identifying the available evidence about the knowledge on the quality of life of the elderly with impaired physical mobility between 2001 and 2011. Data collection happened in the LILACS, MEDLINE and COCHRANEdatabases. After analytical reading of works, we selected 16 articles for analysis in two thematic categories: quality of life and personal satisfaction, and quality of life and functional capacity. The mobilitylimitations, pain and emotional well-being in the elderly can be attributed to chronic conditions, negatively affecting the quality of life; and the elderly who report a decreased quality of life, are those with a higher degree of dependence, influencing social participation and well-being. We suggest the nurse's performance in research on interventions that allow improving the quality of life of the elderly with impaired physical mobility.